Pengaruh Faktor Sosial Demografi dan Gaya Hidup Terhadap Status Obesitas Pada Penduduk Lansia di Provinsi DI Yogyakarta - Indri Puspita Devi; Agus Purwoto (Seminar Nasional Official Statistics, 2022)
DI Yogyakarta has the highest percentage of elderly in Indonesia. The decreasing of body function in the elderly can inflict nutritional problem. One of the nutritional problems is obesity. Obesity increase the risk of getting affected non-communicable diseases, productivity decrease, and the rise in health expences. The purpose of this study was to determine the effect of sociodemographic and lifestyle on the obesity status of the elderly in DI Yogyakarta Province in 2018. This study use Riskesdas 2018 raw data . The sample used is 1717 elderly in DI Yogyakarta Province. This study use binary logistic regression method. The results obtained from this study is 23.82 percent of elderly in DI Yogyakarta Province were obese. Classification of residence area, age, fruit consumption were positively associated with obesity status of the elderly. Inversly gender, education, smoking and physical activity were negatively associated with obesity status of the elderly.